Berberine in Combination with Insulin Has Additive Effects on Titanium Implants Osseointegration in Diabetes Mellitus Rats. (13th December 2015) - Lu, Li; Zhijian, Huang; Lei, Li; Wenchuan, Chen; Zhimin, Zhu
Abstract : This study evaluated the effects of berberine in combination with insulin on early osseointegration of implants in diabetic rats. Fifty male Sprague-Dawley rats were randomly divided into 5 groups: healthy rats were used as control (HC), and streptozotocin-induced diabetic rats were treated with insulin, berberine, berberine + insulin (IB), or no treatment. Each rat received one machined-surface cp-Ti implant into the right tibia and was given insulin injection and/or gavage feeding with berberine daily for 8 weeks until being sacrificed. Serum levels of alkaline phosphatase (ALP) and bone gamma-carboxyglutamic acid-containing protein (BGP) were analyzed in each group. Peri-implant mineral apposition was marked by fluorochrome double-labeling and osseointegration was histomorphologically examined. The ALP and BGP levels decreased in diabetic rats but were successfully corrected by insulin and berberine combined treatment. Moreover, untreated diabetic rats had less labeled mineral apposition and impaired osseointegration. In contrast, Groups I, B, and IB were observed with increased peri-implant bone formation. The combination treatment of insulin and berberine was more effective than each administrated as a monotherapy. These results suggest that berberine combined with insulin could promote osseointegration in diabetic rats, thereby highlighting its potential application to patients, though further studies are needed.